Cutaneous Anthrax: What is the Hallmark? - Dhani Redhono Harioputro; Arie Kusumawardani; Iin Novita; Evi Nurhayatun; Rahajeng N Tunjungputri; Erni Juwita Nelwan (Acta Medica Indonesiana)
A 71-year-old man complained of a blackish wound under his left eye, which began with fever and reddish spots after helping to slaughter a cow and cut its meat. The fever occured especially in the afternoon to evening, and is not accompanied by chills and sweating. On day 4 of fever onset, the fever diminished and the spots progressively widened with swelling. On day 7, the lesions on the skin became open wounds that were not purulent and did not bleed. On day 9, a blackish, painless layer appeared over the wounds and widened, further covering their surface. Upon presentation, the patient’s general condition was good, with normal vital signs and temperature. He presented with a solitary ulcer accompanied by edema, sized 1 cm x 3 cm, not hyperemic, firm border, flat edge, and covered with blackish eschar. Blood tests revealed normal levels of hemoglobin, leukocyte, platelets, kidney and liver function. The anti-anthrax protective antigen (anti-PA) IgG level is found to be seropositive with a level of 85 U/ml. Gram staining of the tissue underneath the eschar found Gram-positive rod bacteria in reddish-purple color. The patient was clinically diagnosed with probable cutaneous anthrax, and was treated with amoxicillin 500 mg orally t.i.d. for three days and paracetamol 500 mg if fever developed. The tissue sample was sent to a laboratory with Bio Safety level 3 facilities for microbiological culture, with the results of Bacillus anthracis growth. On day three after antibiotic administration, the wound was smaller (0.5 cm x 1.5 cm), firm border, flat edge, with a bit of edema above it. The eschar was thickened, painless, not purulent nor bleeding. Antibiotic administration is continued for another three days with amoxicillin 500 mg orally t.i.d. On day 6 of antibiotic administration, the eschar began to peel off, and antibiotics were stopped. On the 10th day, the eschar peeled off entirely without leaving a mark. Early diagnosis is crucial in preventing the spread that may lead to more cases. Clinical and serological examinations are the spearheads of early detection of anthrax cases. Prompt and appropriate management largely determines the success of therapy.